2023
DOI: 10.46223/hcmcoujs.soci.en.13.1.2287.2023
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties encountered by teachers in using storytelling to teach very young learners

Abstract: Storytelling is widely applied in second language teaching, especially to Very Young Learners (VYLs), as this teaching technique is believed to be highly effective. However, storytelling application in VYLs classrooms may be challenging since these learners possess unique characteristics in terms of second language acquisition, which might cause a variety of difficulties for teachers. This paper examines the difficulties Vietnam - USA Society English Center’s teachers encounter during their storytelling applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…A study conducted in Vietnam found that storytelling application in very young learners' classrooms may be challenging since these learners possess unique characteristics in terms of second language acquisition, which might cause a variety of difficulties for teachers (Doan & Quyen, 2023). The participants encountered certain challenges while delivering storytelling lessons, which mainly stemmed from the students and other subjects, namely teachers and materials.…”
Section: Storytellingmentioning
confidence: 99%
“…A study conducted in Vietnam found that storytelling application in very young learners' classrooms may be challenging since these learners possess unique characteristics in terms of second language acquisition, which might cause a variety of difficulties for teachers (Doan & Quyen, 2023). The participants encountered certain challenges while delivering storytelling lessons, which mainly stemmed from the students and other subjects, namely teachers and materials.…”
Section: Storytellingmentioning
confidence: 99%